A mechanistic model for the softening of coking coal and its use for predicting the dilatation of blends. (1st August 2015) - Jenkins, David R.; Mahoney, Merrick R.
Highlights: A phenomenological model of the dilatometer test was developed. The model predicts the whole dilatation curve, based on three parameters for the coal sample. The model matches very well with measured data for single coals. The model is able to predict the dilatation of blends, where the components of the blend all expand. In the case that some components do not expand, they appear to affect the expansion of the other components. Abstract: Models of gas evolution and gas transport within softened coal particles, combined with bubble growth within the particles and gas flow between the particles, are used to develop a phenomenological model of the process of contraction and dilatation of coal samples in a dilatometer test. The model is fitted to dilatometer curves for a range of different coals, in order to determine unknown parameters of the model. The model is shown to provide excellent fits to the measured data for these coals, validating the assumptions underlying it. Finally, the model is used to predict the dilatation of blends. The comparison of the predictions with measured dilatation of blends is good for some cases, but there are discrepancies when non-expanding coals comprise a significant proportion of the blend. A hypothesis for the effect of the non-expanding coals upon the dilatation is proposed.